Hybrid imagination: a study of Mohja Kahl`s ?Emails from Scheherazad?and ?The Girl in the Tangerine Scarf? - Mansour Hasabelnaby, Magda (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper attempts to investigate the hybrid imagination in selected works by Mohja Kahf, a Syrian-American poet (born 1967, Damascus, Syria) . The term hybrid imagination is coined by the researcher drawing on both 18th century Romanticism and the contemporary post-colonial theory.
Keywords: Kahf, Mohja (1967- ); Arab-American literature; hybridity; post-colonial literature; moslem women writers